Individual rationality versus social effects: A case of on-the-job training - Worek, Barbara (Journal of Public Governance, 2014)
Human capital development constitutes the principal challenge facing the Polish society and economy, mainly in the context of population ageing which will be observed in the present decade. The outcomes of recent research and analyses have shown that the level of adult involvement in increasing professional skills in Poland is still too low in relation to the expected needs of the labour market and to the strategic objectives. It is therefore necessary to define the factors determining educational activities of adults, in particular the ones related to the skills required in the labour market. Due to their interdisciplinary character, the problems may be considered from a number of aspects. In the present article an attempt has been made to focus on the circumstances in which rationally acting actors: employers and employees, are inclined to invest in professional skills development; when they might be interested in spending more in training; and how varied institutional factors may affect training strategies of employers and employees.